2015
DOI: 10.1021/cb500792b
|View full text |Cite
|
Sign up to set email alerts
|

Manganese and Microbial Pathogenesis: Sequestration by the Mammalian Immune System and Utilization by Microorganisms

Abstract: Bacterial and fungal pathogens cause a variety of infectious diseases and constitute a significant threat to public health. The human innate immune system represents the first line of defense against pathogenic microbes and employs a range of chemical artillery to combat these invaders. One important mechanism of innate immunity is the sequestration of metal ions that are essential nutrients. Manganese is one nutrient that is required for many pathogens to establish an infective lifestyle. This review summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 109 publications
2
109
0
Order By: Relevance
“…For Mn in nucleus and cytoplasm, an increasing concentration was observed for both these cell compartments, suggesting an uptake of this element from the extracellular environment under PMA-stimulation. Manganese is considered as a nutrient that is required for many pathogens to establish an infective lifestyle and sequestered by neutrophil calprotectin [37]. In absolute terms, we found the Mn concentration in the entire neutrophils gradually increasing from 8.7 to 13.4 ppm after 2 h PMA stimulation and in the nuclei even from 34.2 to 90.9 ppm (for the cytoplasm uncertainty intervals were too large to draw sound conclusions).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…For Mn in nucleus and cytoplasm, an increasing concentration was observed for both these cell compartments, suggesting an uptake of this element from the extracellular environment under PMA-stimulation. Manganese is considered as a nutrient that is required for many pathogens to establish an infective lifestyle and sequestered by neutrophil calprotectin [37]. In absolute terms, we found the Mn concentration in the entire neutrophils gradually increasing from 8.7 to 13.4 ppm after 2 h PMA stimulation and in the nuclei even from 34.2 to 90.9 ppm (for the cytoplasm uncertainty intervals were too large to draw sound conclusions).…”
Section: Resultsmentioning
confidence: 74%
“…Manganese for example, shows an overall increase in concentration at a much lower rate of 2.4 ppm per hour , suggesting an extracellular uptake from the environment. The concentration increase could be related to the sequestration of this metal by the protein calprotectin to prevent it from being harvested by pathogens [37]. Fe showed a linear ( r 2 = 0.67) weight fraction decrease in the nucleus of -6.9 ppm per hour , probably related to decondensation of the nucleus throughout stimulation and release of its content in the extracellular surroundings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Site directed mutagenesis experiments also showed that two His residues in the S100A9 C-terminal tail (His103, His105) are required for high affinity Mn 2+ binding (Brophy et al, 2013; Damo et al, 2013). As noted above, there is energetic coupling of transition metal binding and Ca 2+ binding; the Mn 2+ affinity of CP under limited Ca 2+ availability ( K d >550 nmol L −1 ) is weaker than in the presence of Ca 2+ ( K d =194 nmol L −1 ) (Brophy and Nolan, 2015; Damo et al, 2013). The origin of this allosteric effect has yet to be established, although it is conceivable that binding of Ca 2+ results in reorganization of the structure and/or dynamics of key side chains to better facilitate Mn 2+ binding.…”
Section: Binding Of Manganesementioning
confidence: 90%
“…Vertebrate host has evolved powerful strategy, termed nutritional immunity, to limit proliferation of invading pathogens by sequestering essential nutrients [85]. One of the best characterized examples of nutritional immunity is transition-metal-ion sequestration in which metal ions are predominantly trapped by host metal-binding proteins [86]. To combat with host defensive system, microorganism employs mechanisms to maintain intracellular metal homeostasis.…”
Section: Antibodies Against Nutrient Transporter Proteinsmentioning
confidence: 99%